Eugenika w doktrynie nazizmu - Kaniuk, Emilia Anna (Acta Universitatis Lodziensis. Folia Historica, 2013)
Eugenics is not a nineteenth-century invention. You can talk about it since the appearance of the first people on earth. It had no name yet, but with no doubt it accompanied human being from the beginning. Nineteenth century gave eugenics a name and scientific nature. However, overinterpretation of Nazism made eugenics a pseudoscience. Consequently, this led to the fact that the scientific community turned away from eugenics forever for the sake of the Holocaust. Article titled “Eugenics in the doctrine of Nazism” refers primarily to the theoretical assumptions of eugenics in the context of Nazism. It was presented as a scientific field, which operated in the world for a long time before Adolf Hitler came to power. Then focused solely on the theoretical concepts acquired by the Third Reich. It presented how eugenics influenced the Führer and the program initiated by the purity of the breed, which grew out of the utopian vision of superman. These opinions have been shaped largely by eugenic literature, which was successful, among others in the USA. The original eugenics ideas specified by Francis Galton were significantly different from the ideology outlined by Adolf Hitler's Nazi’s time. The leader of the Third Reich, creating a masterpiece of his life – “Mein Kampf”, used scientific arguments to the propaganda of his book. The work itself was not extensive in terms of form or content. However, recourse to eugenics as a scientific field has led to tangible results. Eugenics became the basis of the purity of the breed, which outlined the features that superman should have. Theoretical use of eugenics turned out to be disastrous in practice, initially just in the Third Reich. Subsequently, the program was extended to the countries occupied by Nazi Germany.